Positive Predictive Value of Benign Prostatic Hyperplasia and Acute Urinary Retention in the Danish National Patient Registry: A Validation Study - Bengtsen, Maria Bisgaard (Clin Epidemiol, 2020)
BACKGROUND AND AIM: Benign prostatic hyperplasia comprises a significant burden to ageing men due to frequently associated lower urinary tract symptoms and the risk of developing serious complications, such as acute urinary retention. Healthcare databases are a valuable source of epidemiological research; however, continuous validation of definitions is imperative. We examined the positive predictive values of International Classification of Diseases, 10th Revision (ICD-10), diagnostic coding for benign prostatic hyperplasia and acute urinary retention in men in the Danish National Patient Registry. METHODS: We investigated a random sample of 100 men diagnosed with benign prostatic hyperplasia and 100 men diagnosed with acute urinary retention between 2011 and 2017 in the Central Denmark Region. Using medical record review as reference standard, we estimated the positive predictive value with corresponding 95% confidence intervals (CI) overall and stratified by age, type of hospital (university hospital vs regional hospital), type of hospital contact (inpatient, outpatient or emergency room), calendar year group (2011–2013, 2014–2017), and department (department of urology, geriatrics, endocrinology or emergency room). RESULTS: Medical records were available for all 200 sampled patients. We found an overall positive predictive value (PPV) of 95% (95% CI: 89–98%) for benign prostatic hyperplasia and 98% (95% CI: 93–99%) for acute urinary retention. The PPVs were consistent across age, type of hospital, type of hospital contact, calendar year group, and department. CONCLUSION: The PPVs of ICD-10 codes for benign prostatic hyperplasia and acute urinary retention recorded in the Danish National Patient Registry are high.